2012
DOI: 10.1371/journal.pone.0038965
|View full text |Cite
|
Sign up to set email alerts
|

Paneth Cells in Intestinal Homeostasis and Tissue Injury

Abstract: Adult stem cell niches are often co-inhabited by cycling and quiescent stem cells. In the intestine, lineage tracing has identified Lgr5 + cells as frequently cycling stem cells, whereas Bmi1 +, mTert +, Hopx + and Lrig1 + cells appear to be more quiescent. Here, we have applied a non-mutagenic and cell cycle independent approach to isolate and characterize small intestinal label-retaining cells (LRCs) persisting in the lower third of the crypt of Lieberkühn for up to 100 days. LRCs do not express markers of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 53 publications
(116 reference statements)
4
124
0
Order By: Relevance
“…The role of Lgr5+ and Paneth cells in the response to radiation damage is of great recent interest (Buczacki et al, 2013;Hua et al, 2012;Metcalfe et al, 2014;Roth et al, 2012). We addressed the role of Wnt production in the radiation response and found that global pharmacologic, but not epithelial-specific, inhibition of PORCN caused markedly increased sensitivity to radiation stress in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Lgr5+ and Paneth cells in the response to radiation damage is of great recent interest (Buczacki et al, 2013;Hua et al, 2012;Metcalfe et al, 2014;Roth et al, 2012). We addressed the role of Wnt production in the radiation response and found that global pharmacologic, but not epithelial-specific, inhibition of PORCN caused markedly increased sensitivity to radiation stress in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that intestine and skin not only contain classic tissue-specific stem cells that maintain tissue homeostasis but also independent cell populations that generate the same range of differentiated cells in response to wound healing (1,2). We have also learned that stromal cues not only dictate which cell population will respond to specific environmental signals but also which phenotypes will manifest.…”
mentioning
confidence: 99%
“…Accordingly, in vivo inactivation of the Vdr gene in Lgr5 hi cells compromises their ability to lineage trace whereas lower dietary vitamin D3 affects both their stem cell function and their capacity to form tumours upon targeted mutation of the Apc gene (9). In view of these data and of previous observations substantiating the "top-down" model of intestinal tumour formation, other stem cell compartments, as well as differentiated cell types are likely capable, upon stress factors of various nature, of re-entering the cell cycle and of acquiring stem cell characteristics as part of the tissue adaptive response to this particular environmental factor, as well as perhaps others (10,11). The notion that Lgr5 hi cells do not efficiently function as intestinal stem cells at vitamin D3 levels characteristic of the vast majority of the human population clearly and inevitably affect not only the conclusions reached by the Beyaz et al study relative to the changes in these cells as the cause of high fat/obesity increased colon cancer incidence in the human population, but those of many other mouse studies of intestinal stem cell biology based on standard chow diets.…”
Section: Commentary On Nutritionmentioning
confidence: 70%